PENGARUH UPAH MINIMUM REGIONAL DAN RASIO INFRASTRUKTUR TERHADAPKESENJANGAN DISTRIBUSI PENDAPATAN DI INDONESIA - Siti Nurul Noviana (Jurnal Akuntansi AKTIVA, 2020)
This study aims to examine the impact of region minimum wage and infrastructure ratio onIncomeDistribution Gap in Indonesia. This study uses panel data for the period 2011-2017 and consists of 33provinces, except North Kalimantan Province because it is a new province. By using fixed effectpanel data regression analysis, with dependent variable is gini index. While independent variable areregional minimum wage and infrastructure ratio.On the one hand, based on hypothetical test, theresults show that the regional minimum wage and infrastructure ratio have a negative and significanteffect on the income distribution gap in Indonesia. On the other hand, based on the individual effectstest, the large islands such as Sumatera, Java, Kalimantan, Sulawesi, Bali, Maluku, and Papua have apositive effect on the gini ratio. This shows that there is an impact of the infrastructure ratio functionand regional minimum wages in increasing the distribution of income as measured by the gini index.